Ethical Principles of Autonomy for Hypertension Patients : A concept analysis. - Endang Triyanto; Sidik Awaludin; Zuhariah Felis (Asia Pacific Journal of Health Management)
Background: Autonomy is a fundamental ethical principle within the nursing profession. It plays a significant role in patients' decision-making processes when seeking nursing interventions. In the context of hypertensive individuals, autonomy pertains to their capacity to manage and regulate their hypertensive condition. This encompasses the independent decision-making related to medications, lifestyle adjustments, and overall care.